THE IMPACT OF THE PANDEMIC COVID-19 ON THE STATE OF INTERNATIONAL POLITICS AND SECURITY - Thuy, Loc Thi (International Journal of Research -GRANTHAALAYAH, 2021)
From the beginning of the year 2020 until now, the Covid-19 pandemic has heavily, deeply and comprehensively impacted the state of international politics and security in both positive and negative directions. On one hand, the pandemic has encouraged nations to strengthen cooperation in order to effectively deal with the risks that it brought; on the other hand, it has contributed to a rise in competition as well as opposition between countries and global powers alike, especially between the U.S. and China, in multiple politics and security-related issues. In the coming times, the state of international politics and security is predicted to witness many changes, especially in the context where the U.S. is highly expected to adjust its policies. For this text, the writer will place an emphasis on providing in-depth analysis on the negative impacts of the Covid-19 pandemic on the state of international politics and security, and therefore provide commentary on the trends of the state of international politics and security in the coming times.